Contribution of Solar Energy at Ship Power System in Reducing Emission and Fuel Consumption - Diah Zakiyah; Indra Jaya; Ayi Rahmat (Dinasti Publisher, 2024)
International Maritime Organization has entered into force several regulations to lessen the carbon footprint of maritime transport. Energy Efficiency Existing Ship Index (EEXI) is utilized to sustain continuously increased energy efficiency and CII (Carbon Intensity Indicator) is utilized to measure carbon emissions and rating boundary of ships. Every ship must have strategies to reduce fossil fuel consumption to meet the minimum required carbon emissions. Solar energy can be a viable solution for reducing emissions and fuel consumption in ship power systems. Solar panels can be installed on the ship's deck or other suitable areas to generate electricity. This electricity can be used for auxiliary systems such as lighting, ventilation, and onboard equipment, reducing the reliance on conventional fuel-powered generators. Solar energy can also be integrated into hybrid power systems, combining it with traditional fuel-powered engines or other renewable energy sources like wind power. This hybridization can optimize energy generation and reduce the consumption of fossil fuels. This paper will review several studies and applications of solar energy as part of ship power system, and analyze the contributions in supporting reduction of carbon emissions.